Bioacústica de baleias cachalotes (Physeter macrocephalus Linnaeus, 1758) com ênfase no oceano Atlântico Sul ocidental - Amorim, Thiago Orion Simões (Universidade Federal de Juiz de Fora (UFJF), 2017)
Sperm whales live in multilevel societies in which the fundamental social level is the nearly-permanent social units of females and immature. The largest level is the clan constituted by social units that share a common coda repertoire. This work described the vocal repertoire of sperm whales from western South Atlantic Ocean recorded between 2011 and 2016. Rainbow Click was used to mark and automatically measured the inter-click intervals of codas, which were used to quantify similarity between repertoires through two different approaches: one categorical and one continuous. The former was used to calculate the multivariate similarity of two codas with the same number of clicks through the Euclidean distance, the latter classified codas into types using the hierarchical clustering algorithm OPTICSxi. The analysis showed two evident clans, North and South, distinct in their repertoires characterizing geographic variation in vocal behaviour of sperm whales in the western South Atlantic. The clan North presented a predominant production of 5R type not found in clan South, which repertoire was dominated by long codas with descending inter-click intervals (10D1, 10D2, 11D1, 11D2, 12D1, 12D2, 13D1 e 13D2). The 5R codas is predominant in the island of Dominica (Caribbean Sea), suggesting that the predominance of this type acts as a symbolic marking of clan North and is a result of cultural transmission maintaining the conformism through social learning in the usage of most common coda types. This cultural transmission occurs between individuals that preferentially interact and behave similarly. The results of this work corroborated the hypothesis that social boundaries, here the clan level, are maintained by cultural identities and that the study of codas is a reliable way in accessing the population structure. As cachalotes vivem em sociedades multinível cujo nível social fundamental é a unidade social quase permanente constituída por fêmeas adultas e indivíduos jovens. O nível social mais alto corresponde ao clã ...